2014
DOI: 10.1089/dna.2013.2236
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in Interleukin Genes and Susceptibility to IgA Nephropathy: A Meta-Analysis

Abstract: Many existing studies have demonstrated that genetic variants in interleukin (IL) genes might have an impact on an individual's susceptibility to IgA nephropathy (IgAN); but individually published results are inconclusive. This meta-analysis aimed to derive a more precise estimation of the relationships between IL genetic variants and IgAN risk. We searched CISCOM, CINAHL, Web of Science, PubMed, Google Scholar, EBSCO, Cochrane Library, and China BioMedicine (CBM) and China National Knowledge Infrastructure (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…IL1RN and COL4A2 belong to class I, which were altered in IgAN vs. LD group. IL1RN is involved in autoinflammatory disease ( 24 ) and may contribute to the risk of IgAN ( 25 , 26 ). COL4A2 is a member of the collagen type IV family that may be effective as a marker of renal dysfunction ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL1RN and COL4A2 belong to class I, which were altered in IgAN vs. LD group. IL1RN is involved in autoinflammatory disease ( 24 ) and may contribute to the risk of IgAN ( 25 , 26 ). COL4A2 is a member of the collagen type IV family that may be effective as a marker of renal dysfunction ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a Galbraith plot was used to identify and exclude those studies responsible for heterogeneity. Sensitivity analysis was principally performed by sequential omission of individual studies or of those containing data that deviated from HWE (Liu et al, 2014). Subgroup analyses were performed based on sample sizes, and publication bias was assessed by visual inspection of funnel plots and the Begg's rank correlation method (P < 0.05 was considered statistically significant).…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analysis results revealed that variants of the IL-1 and IL-1RN genes were correlated with an increased risk of IgAN. However, similar results were not observed for the genes of IL-6 , IL-10 , or IL-22R [28]. Considering these conflicting results, the role of IL-10 in the pathogenesis of IgAN is worth further investigation.…”
Section: Introductionmentioning
confidence: 86%